The effect of partial replacement of maltodextrin with vegetable fibres in spray-dried white asparagus powder on its physical and aroma properties. (15th September 2021) - Siccama, Joanne W.; Pegiou, Eirini; Eijkelboom, Nienke M.; Zhang, Lu; Mumm, Roland; Hall, Robert D.; Schutyser, Maarten A.I.
Graphical abstract: Highlights: Juice from asparagus cut-offs can be used to make spray-dried asparagus powder. Asparagus fibre can be applied to partially replace maltodextrin as a carrier matrix. Higher initial solids led to lower residual moisture and improved aroma retention. Low maltodextrin replacement did not strongly affect the volatile profile of the powders. Abstract: Asparagus concentrate was spray-dried in different carrier formulations in which maltodextrin was partially replaced by cellulose-based carriers, i.e. asparagus fibre, citrus fibre or microcrystalline cellulose. This replacement was limited to a maximum level of 3% w/w for asparagus and citrus fibres, and 10% w/w for microcrystalline cellulose, due to fibre insolubility and increased viscosity of the feed. Powders obtained from feed solutions with an initial solids content of 40% w/w showed better physical properties and aroma retention than 30% w/w. Partial replacement of maltodextrin by cellulose-based carriers resulted in powders with similar physical properties as the control and did not detrimentally influence the aroma profiles as analyzed by headspace solid-phase microextraction and gas chromatography–mass spectrometry. This research shows that fibre obtained from asparagus waste streams could potentially be used as a carrier to produce spray-dried asparagus powder with retained key asparagus volatiles such as 2-methoxy-3-isopropyl pyrazine.